Penerapan Teknologi Kalibrasi Alat Medis Berbasis Standar untuk Menjamin Keandalan Diagnostik di Puskesmas Banjarbaru Selatan - Rezky Rahmadany Rachman (Universitas Lambung Mangkurat, 2025)
AbstractThe main problem faced by Banjarbaru Selatan Community Health Center (Puskesmas) is the potential inaccuracy of primary medical devices following relocation, exacerbated by the fact that the device calibration period will expire in June 2025. This risks compromising diagnostic reliability. The objective of this service is to ensure the accuracy of medical devices according to standards, and to enhance health personnel's awareness and student competency through socialization, training, and the implementation of standard-based medical device calibration. The activity was conducted on July 31, 2025, at Puskesmas Banjarbaru Selatan. The subjects were 20 health personnel, 5 students (as training participants and assisting executors), and five types of calibrated medical devices (10 Tensiometers, 2 Baby Scales, 2 Adult Scales, and 1 USG). Calibration involved the proposing team and the Medical Device and Health Facility Testing Agency (LPAFK). The results showed that all devices were successfully calibrated, obtained official calibration certificates, and were labelled, supported by increased health personnel understanding and students' practical experience, thus ensuring measurement reliability and guaranteeing the quality of health services at the Puskesmas.Keywords: Accuracy; Calibration; Medical Devices; Precision; Quality Assurance AbstrakPermasalahan utama Puskesmas Banjarbaru Selatan adalah potensi ketidakakuratan alat medis utama pasca relokasi gedung baru, diperburuk dengan fakta bahwa masa berlaku kalibrasi alat tersebut akan habis pada Juni 2025. Hal ini berisiko mengganggu keandalan diagnostik. Tujuan pengabdian ini adalah menjamin akurasi alat medis sesuai standar, serta meningkatkan kesadaran tenaga kesehatan dan kompetensi mahasiswa melalui sosialisasi, pelatihan, dan pelaksanaan kalibrasi alat medis berbasis standar. Kegiatan dilaksanakan pada 31 Juli 2025 di Puskesmas Banjarbaru Selatan. Subjek pengabdian meliputi 20 tenaga kesehatan, 5 mahasiswa (sebagai peserta pelatihan dan pelaksana asistensi), serta lima jenis alat medis yang dikalibrasi (10 Tensimeter, 2 Timbangan Bayi, 2 Timbangan Dewasa, dan 1 USG). Pelaksanaan kalibrasi melibatkan tim pengusul dan Lembaga Pengujian Alat dan Fasilitas Kesehatan (LPAFK). Hasilnya, seluruh alat berhasil terkalibrasi, memperoleh sertifikat kalibrasi resmi, dan dipasang label, didukung peningkatan pemahaman tenaga kesehatan serta pengalaman praktis mahasiswa, sehingga memastikan keandalan pengukuran dan menjamin mutu pelayanan kesehatan di Puskesmas.Kata Kunci: Akurasi; Alat Medis; Kalibrasi; Penjaminan Mutu; Presisi